Influence of the corneal biological covering with cryocorserved amniotic membrane on the peculiarities of the course of modeled bacterial keratitis (Ukrainian Journal of Ophthalmology, 2026)
Introduction. The study is important due to insufficient investigation of peculiarities of anti-inflammatory effect of the amniotic membrane in treatment of bacterial keratites. Objective. To investigate in experiment the influence of the corneal biological covering with the amniotic membrane cryoconserved by a new technology on the peculiarities of the course of modeled bacterial keratitis. Material and methods. Transplantation of the amniotic membrane cryoconserved by the new technology was performed in 30 Chinchilla rabbits (30 eyes) weighing 2.5–3.0 kg on the developed model of bacterial keratitis of the moderate degree of severity. Results. In one month all animals showed absence of the amniotic membrane and the corneal surface was epithelized. It was characterized by formation of nonintensive keratoleucoma with residual infiltration in 3 rabbits (3 eyes). There was no vascularization in all animals. The histological samples showed complete epithelization with restoratopn of the corneal stroma. Edema and lymphocyte-histocytic infiltration were absent. There were preserved invaginations at the level of basal membrane (corneal plug). Conclusion. It was established on the model of bacterial keratitis that amniotic membrane transplantation, cryoconserved by the developed technology stimulated epithelization being a biological covering and contributes to elimination of edema and signs of inflammatory reaction of the cornea.
Keywords: Bacterial keratitis; amniotic cryoconserved membrane; experiment